Sanksi Ta’zir Terhadap Perilaku Eksploitasi Diri Manusia Silver Perspektif Maqashid Syari’ah - Daiyatul Mardiyah; Noor Azizah (Institut Agama Islam Negeri (IAIN) Bone, 2025)
This research emphasizes the importance of synergy between positive law and Islamic criminal law in formulating policies that protect perpetrators while maintaining public order. Silver men, which are individuals who paint their entire body with metal paint and appear in public spaces to beg, have become a common sight in various major cities in Indonesia. This practice not only poses health risks due to exposure to hazardous chemicals, but also raises social and legal problems. Based on article 504 of the Criminal Code, begging in public places is a criminal offense that can be punished with imprisonment. However, a positive legal approach focuses more on enforcement than coaching. This study aims to analyze the self-exploitation behavior of silver humans from the perspective of Islamic criminal law with a focus on ta'zir sanctions and the principles of maqashid shari'ah. The research method used is a normative approach with qualitative analysis of fiqh literature, maqashid shari'ah and relevant laws and regulations. The results of the study found that the self-exploitation behavior of silver humans is contrary to the five main goals of sharia: to protect religion (hifz al-din), soul (hijz al-nafs), intellect (hifz al-'aql), heredity (hifz al-nasl), and property (hifz al-mal). Therefore, the imposition of ta'zir sanctions that are educational and rehabilitative in nature is more appropriate to create benefits, rather than just imprisonment as stipulated in the Criminal Code. Penelitian ini menekankan pentingnya sinergi dari hukum positif dan hukum pidana islam dalam merumuskan kebijakan yang melindungi pelaku sekaligus menjaga ketertiban umum. Manusia silver yaitu individu yang mengecat seluruh tubuhnya dengan cat logam dan tampil diruang publik untuk mengemis, telah menjadi pemandangan umum diberbagai kota besar Indonesia. Praktik ini tidak hanya menimbulkan resiko kesehatan akibat paparan bahaya kimia berbahaya, tetapi juga memunculkan permasalahan sosial dan hukum. Berdasarkan pasal 504 KUHP mengemis ditempat umum merupakan tindak pidana yang dapat dikenakan pidana kurungan. Namun pendekatan hukum positif lebih menitikberatkan pada penindakan daripada pembinaan. Penelitian ini bertujuan menganalisis perilaku eksploitasi diri manusia silver dari perspektif hukum pidana islam dengan fokus pada sanksi ta’zir dan prinsip maqashid syari’ah. Metode penelitian yang digunakan adalah pendekatan normatif dengan analisis kualitatif terhadap literature fiqih, maqashid syari’ah dan peraturan perundang-undangan yang relevan. Hasil penelitian menemukan bahwa perilaku eksploitasi diri manusia silver bertentangan dengan lima tujuan utama syariat: menjaga agama (hifz al-din), jiwa (hijz al-nafs), akal (hifz al-‘aql), keturunan (hifz al-nasl), dan harta (hifz al-mal). Oleh karena itu, penjatuhan sanksi ta’zir yang bersifat mendidik dan rehabilitative lebih sesuai untuk menciptakan kemaslahatan, dibandingkan sekedar hukuman kurungan sebagaimana diatur di KUHP.